2006
DOI: 10.1093/bja/ael169
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral haemodynamic changes during propofol–remifentanil or sevoflurane anaesthesia: transcranial Doppler study under bispectral index monitoring

Abstract: Propofol-remifentanil anaesthesia induced a dose-dependent low-flow state with preserved cerebral autoregulation, whereas sevoflurane at high doses provided a certain degree of luxury perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 37 publications
7
74
1
2
Order By: Relevance
“…The presedation Glasgow Coma Score (GCS) at admission to the ICU was 15 in eight patients, 12-14 in six patients, and 9 in two patients, and symptoms of encephalopathy, ranging from confusion to delirium and unconsciousness, were present in 10 patients prior to sedation. Propofol, fentanyl, and/or remifentanil were used as sedatives-analgesics in 14 patients, none of which have been found to affect cerebral autoregulation in previous studies of elective surgical patients (9,35,39). Two patients received all three, seven received two, and five received one of these drugs.…”
Section: Methodsmentioning
confidence: 99%
“…The presedation Glasgow Coma Score (GCS) at admission to the ICU was 15 in eight patients, 12-14 in six patients, and 9 in two patients, and symptoms of encephalopathy, ranging from confusion to delirium and unconsciousness, were present in 10 patients prior to sedation. Propofol, fentanyl, and/or remifentanil were used as sedatives-analgesics in 14 patients, none of which have been found to affect cerebral autoregulation in previous studies of elective surgical patients (9,35,39). Two patients received all three, seven received two, and five received one of these drugs.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the use of inhalational halogenated anesthetics may cause an impairment of cerebral autoregulation [10]. This is a critical problem for the patients of moyamoya disease, however, sevoflurane does not affect cerebral autoregulation less than 1.5 MAC [11,12]. Therefore, we used low concentrations of sevoflurane as a sedative agent until the neonate was delivered.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines recommend that the drugs of choice in patients more than 12 years old requiring prolonged sedation and analgesia during mechanical venti- Several studies have evaluated the effects of propofol on cerebrovascular circulation and CO 2 reactivity [11,[16][17][18][19][20]. These studies, were however, all conducted with anesthetic rather than sedative doses of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Harrison et al [18] examined the effects of target-controlled infusion (TCI) of propofol (mean target concentration was 6.7 ± 1.1 μg·ml −1 ), and found that propofol had no effect on CO 2 reactivity. Conti et al [19] showed that total intravenous anesthesia (TIVA) with propofol-remifentanil preserved cerebrovascular CO 2 reactivity at a BIS level of 50, in which the TCI rate of propofol was 2.7 ± 0.5 μg·ml −1 , and that of remifentanil was 0.18 ± 0.06 μg·kg −1 . In contrast, Eng et al [11] examined the effects of propofol on cerebral CO 2 reactivity.…”
Section: Discussionmentioning
confidence: 99%